Epidermolysis bullosa acquisita and inflammatory bowel disease: a review of the literature. (21st March 2013) - Reddy, H.; Shipman, A. R.; Wojnarowska, F.
Summary We present a review of all previously reported cases of epidermolysis bullosa acquisita (EBA) and inflammatory bowel disease (IBD). We found 42 cases of coincident EBA and IBD in the literature: 35 cases of Crohn disease (CD) and 7 of ulcerative colitis (UC). The clinical and immunopathological features of the cases are described and the demographics collected. In the majority of cases, the diagnosis of IBD predated the development of the skin condition. The association between EBA and IBD was more common for CD than for UC. We discuss the immunopathogenesis of IBD and EBA, and also the link between them, namely type VII collagen.